BizTalk Server 2010 Cookbook. - Wiggers, Steef-Jan (Packt Pub., 2012)
This book will explain step-by-step in each recipe how to, for example, implement a certain orchestration pattern, test a BizTalk artifact, monitor BizTalk with a third party tool, or secure a message. The recipes in this book are easy to understand and follow as the author discusses real-world scenarios. The range of topics covered in this book will bring out the forward-thinking BizTalk developer in you. The examples are supported by relevant background information for ease of understanding. This book is for professional BizTalk Developers and administrators to take their skills to the next.